Mechanical and electrolytic hybrid grinding of metal ceramic composites using coarse diamond grinding wheel. (October 2020) - Lu, Yanjun; Sun, Jiajing; Chen, Fumin; Mo, Rui; Li, Liejun; Gao, Jixiang
Abstract: The application and development of metal ceramic composites have been restricting due to its low grinding efficiency and ground quality. In this paper, the hybrid machining technology combined mechanical with electrolytic grinding based on dressed coarse diamond grinding wheel is proposed to perform efficient and precise grinding of metal ceramic composites. First, the dry electrical discharge dressing technology was used to dress coarse diamond grinding wheel to obtain high grain protrusion and sharp micro-grain cutting edges. Next, the mechanical and electrolytic hybrid grinding process using dressed coarse diamond wheel was developed to grind metal ceramic. Finally, the effects of different process parameters on ground surface topographies and surface roughness were investigated. It is shown that the proposed hybrid grinding method was feasible and can effectively improve the ground surface quality. The experimental results show that the optimal process parameters including the depth of cut, open-circuit voltage and impulse width were 5 μm, 20 V and 400 ns, respectively. Compared with traditional mechanical grinding, the ground surface roughness by the proposed hybrid machining method was improved by about 25%.